2020
DOI: 10.1002/smll.202003799
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Luminescence Alternation of Sub‐30 nm Upconversion Nanoparticles with a Small NaHoF4 Core and Multi‐Gd3+/Yb3+ Coexisting Shells

Abstract: With narrow luminescence peak width, reduced photobleaching, high physical and chemical stability, low toxicity, etc., [4-8] RE-doped UCNPs have been widely utilized in all sorts of fields, [9-17] especially in photoinduced therapies. [18-24] Among these UCNPs, activator (usually Er 3+ , Tm 3+ , Ho 3+) or sensitizer (usually Yb 3+) highly doped ones, provided with unique optical properties like exceptional brightness, single-band emission, lifetime tuning, and so on, [25] which are of great bioapplication pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 75 publications
2
39
0
Order By: Relevance
“…In a biomedical setting, this limitation restricted their optical-based popularization. Importantly, past work has shown that codoping with a broadband absorptive sensitizer was an effective way to mitigate this limitation. , Broadband absorptive sensitizer with d–f electronic transition usually exhibited a large molar extinction coefficient, so the excitation energy could be adequately absorbed, and then radiative transition occurred. Thus, codoping with a broadband absorptive sensitizer could enhance the efficiency of NPs. , In a CaF 2 matrix, CaF 2 :Ce 3+ emission partly overlapped with CaF 2 :Tb 3+ excitation (Figure S5), indicating the 5d energy level of Ce 3+ was matched with the 4f energy level of Tb 3+ .…”
Section: Resultsmentioning
confidence: 99%
“…In a biomedical setting, this limitation restricted their optical-based popularization. Importantly, past work has shown that codoping with a broadband absorptive sensitizer was an effective way to mitigate this limitation. , Broadband absorptive sensitizer with d–f electronic transition usually exhibited a large molar extinction coefficient, so the excitation energy could be adequately absorbed, and then radiative transition occurred. Thus, codoping with a broadband absorptive sensitizer could enhance the efficiency of NPs. , In a CaF 2 matrix, CaF 2 :Ce 3+ emission partly overlapped with CaF 2 :Tb 3+ excitation (Figure S5), indicating the 5d energy level of Ce 3+ was matched with the 4f energy level of Tb 3+ .…”
Section: Resultsmentioning
confidence: 99%
“…With the development of nanotechnology, lanthanide doped UC materials experienced the explosive growth, especially in biological applications [7][8][9] , photon-conversion devices 10,11 , super-resolution nanoscopy [12][13][14] , and information storage and security etc [15][16][17] . Much efforts have been devoted to manipulate UC, and Yb 3+ , Nd 3+_ sensitized energy transfer (ET) and interfacial energy transfer (IET) are recognized as the promising ways to achieve e cient UC luminescence [18][19][20][21][22][23] .…”
Section: Main Textmentioning
confidence: 99%
“…In the past decades, lanthanide-based photon UC has been confirmed to be a promising strategy for addressing many challenging issues, such as highly sensitive temperature sensing, 1,2 dynamic anti-counterfeiting, 3 super-resolution microscopy, 4 deeptissue bio-imaging, [5][6][7] etc. Unfortunately, real-world applications have been hindered due to some limitations (e.g., thermally quenched luminescence 8 ).…”
Section: Introductionmentioning
confidence: 99%